The platelet - Lapetina, Edwardo G.; Bittar, E. E. (Advances in molecular and cell biology ;, 1997)
Platelets have been an important model system in which to study various aspects of signal transduction. In spite of the fact that platelets are anucleated cells, it has been possible to assess the relationship between receptors, transducers and effectors, and specific platelet physiological responses. As a consequence, discrete biochemical events can be related to shape change, aggregation, and secretion. In addition to undergoing these internal biochemical changes, activated platelets express glycoproteins receptors for adhesive proteins on their surfaces; these help consolidation of the initial platelet aggregate to stop bleeding and start repair. When this protective action of platelets is exaggerated, a pathological situation arises. Abnormal platelet function is associated with thrombosis, atherosclerosis, and bleeding disorders. This book deals with the most important aspects of platelet signal transduction that have been revealed in the past few years. Emphasis is given to knowledge gained in the area of glycoprotein receptors or integrins that bind adhesive proteins and play a crucial role in thrombosis. One of these integrins also serves as a collagen receptor on platelets. Collagen and thrombin are primary activators at sites of vascular injury. The main thrombin receptor recently was recognized as a seven trans-membrane domain receptor, and attention is now focused on the development of thrombin receptor antagonists that might prove to be useful in treatment of thrombosis and restenosis. The formation and release of thromboxane A2 n activated platelets help to recruit additional platelets to the injury site; the receptor for thromboxane A2 is a newly discovered seven trans-membrane domain receptor that is also covered in this book. The coupling of platelet receptors to the effectors or second-messenger-producting enzymes is mostly through heterotrimeric and low molecular weight GTP-binding proteins, which have an important role in the stimulation or inhibition of platelet effectors. Two chapters deal with the role of GTP-binding proteins in human platelets. Several chapters are devoted to the effectors, including phospholipases C, A2, D, and phosphatidylinositol 3-kinase; the mobilization of Ca2+; and the formation of cAMP, cGMP, nitric oxide, and the role of the NA+/K+ exchanger. This is integrated with information on the activation of important protein kinases - that is, protein kinase C, Ca2+ -calmodulin-dependent protein kinases, cAMP and cGMP-dependent kinases, and tyrosine kinases - and on how these activities lead to changes in platelet cytoskeleton to cause shape change, aggregation, and secretion.